NIMG-74. MULTIPARAMETER MRI INVESTIGATION OF HIGH-GRADE GLIOMA RESPONSE TO CAR T CELL IMMUNOTHERAPY. (11th November 2019) - Ravi, Harshan; Stringfield, Olya; De Leon, Gustavo; Johnston, Sandra; Rockne, Russell; Badie, Behnam; Brown, Christine E; Swanson, Kristin; Gatenby, Robert; Raghunand, Natarajan
Abstract: INTRODUCTION: Immunotherapy with engineered CAR T cells is a promising new therapy for glioblastoma, for which predictive and prognostic biomarkers are needed to inform effective intervention. Recently, our group analyzed standard-of-care (SOC) MRI images of long-term and short-term glioblastoma survivors and identified six intratumoral "habitats" of which "Habitat 6" was correlated with survival at diagnosis in high-grade glioma. Based on the MRI characteristics of "Habitat 6", viz. high enhancement and high edema, we hypothesized that it could be a marker of tumor immune infiltrates. We are studying longitudinal changes in tumor "habitat" composition on MRIs of subjects with recurrent high-grade glioma treated with CAR T cells engineered to target IL13Ra2. METHODS: MRI scans of the brain were acquired in 6 subjects at 3.0 T at baseline and various times before and after initiation of CAR T cell therapy. FLAIR, T1W and T1W-CE MRI images were registered to T2W images and six intratumoral "habitats" were computed as per our recently published methodology. The six habitats generated at the end of the tumor segmentation process were: "Habitat 1" (low FLAIR, low enhancement), "Habitat 2" (high FLAIR, low enhancement), "Habitat 3" (low FLAIR, medium enhancement), "Habitat 4" (high FLAIR, medium enhancement), "Habitat 5" (low FLAIR, high enhancement), and "Habitat 6" (high FLAIR, high enhancement). RESULTS: Analysis of temporal changes in the six "habitats" shows an initial increase in both "Habitat 4" and "Habitat 6" following CAR T cell therapy initiation. Subjects with higher absolute volumes of "Habitat 6" at the baseline (pre-treatment) showed longer overall survival. Overall survival is a function of absolute "Habitat 6" volume at baseline, its direction of change immediately post-therapy, the duration of any increase in "Habitat 6" post-treatment, and the "Habitat 6" to "Habitat 4" ratio. Additional subjects are being evaluated to further understand these preliminary observations.